Study of T Lymphocytes Infiltrating Peritoneal Metastases in Advanced Ovarian Cancer: Associations With Vascular Endothelial Growth Factor Levels and Prognosis in Patients Receiving Platinum-Based Chemotherapy. Issue 8 (1st November 2009) - Tsiatas, Marinos L.; Gyftaki, Reveka; Liacos, Cristine; Politi, Ekaterini; Rodolakis, Alexandros; Dimopoulos, Meletios-Athanasios; Bamias, Aristotelis
Abstract : Introduction: The presence of CD3 + tumor-infiltrating lymphocytes (TILs) has been found to correlate with improved survival in epithelial ovarian cancer, but the association of TIL subpopulations with clinical outcome remains controversial. We performed a prospective analysis of TIL subpopulations from patients with epithelial ovarian cancer and their activation status and studied their association with prognosis. Methods: Flow cytometric analysis was performed on TIL subpopulations isolated from 45 fresh ovarian tumor specimens, obtained during surgery, after mechanical dissociation and enzymatic degradation. Vascular endothelial growth factor and tumor necrosis factor α levels in ascites and serum were measured by enzyme-linked immunosorbent assay. Results: Significantly increased numbers of CD56 + cells (natural killer and natural killer-like T cells; P = 0.045), activated CD4 + HLA-DR + cells ( P = 0.046), and activated CD8 + CD25 + cells ( P = 0.028) were found in serous and endometrioid carcinomas compared with mucinous and clear cell carcinomas. A high percentage of CD4 + CD25 hi cells (regulatory T cells) and activated CD4 + HLA-DR + cells significantly associated with improved median overall survival (not reached vs 35 months [ P = 0.0241] and not reached vs 35 months [ P = 0.0144], respectively) and median progression-free survival (30 months vs 14 months [ P = 0.0819] and 30 months vs 13 months [ P = 0.0479], respectively). Vascular endothelial growth factor ascites levels were inversely correlated with CD14 + ( ρ = −0.529, P = 0.001), whereas HLA-DR8 + CD8 lymphocytes were inversely correlated with both ascites and serum vascular endothelial growth factor levels ( ρ = −0.494, P = 0.006, and ρ = −0.586, P = 0.037, respectively). Conclusions: The presence of regulatory T cells and activated CD4 + cells within the tumor microenvironment is associated with improved overall and progression-free survival in patients with ovarian cancer.